2022
DOI: 10.1039/d2sc00837h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsymmetrically tetrasubstituted pyrroles and studies of AIEE in pyrrolo[1,2-a]pyrimidine derivatives

Abstract: Pyrroles are among the most important heterocycles in pharmaceuticals and agrochemicals. Construction of pyrrole scaffolds with different substituents and free NH group however, is challenging. Herein, a metal-free method for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Pyrroles can be used to prepare cyano-pyrrolo[1,2-a]pyrimidines, which have properties of photoelectricity (Scheme 1d). 12 Although these strategies allow for the synthesis of cyanated nitrogen heterocyclic compounds, there are still some issues that remain to be resolved: (1) these methods are useful for the synthesis of cyano-substituted nitrogen heterocycles, but it is not possible to obtain 2-cyanoimidazo[1,2-a]pyridine; (2) the scope of the reaction substrate is limited, and it is hard to expand the substrate for functionalizing C−H on the pyridine ring;…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pyrroles can be used to prepare cyano-pyrrolo[1,2-a]pyrimidines, which have properties of photoelectricity (Scheme 1d). 12 Although these strategies allow for the synthesis of cyanated nitrogen heterocyclic compounds, there are still some issues that remain to be resolved: (1) these methods are useful for the synthesis of cyano-substituted nitrogen heterocycles, but it is not possible to obtain 2-cyanoimidazo[1,2-a]pyridine; (2) the scope of the reaction substrate is limited, and it is hard to expand the substrate for functionalizing C−H on the pyridine ring;…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have succeeded in synthesizing or functionalizing azacycle compounds. In addition, several methods of synthesis for aromatic azacycles have been reported [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. However, these methods still have several drawbacks such as being time-consuming, requiring a high temperature, expensive additives, and/or organic solvents, and/or having low chemoselectivity properties [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this difference is also observed in the analysis of some properties such as fluorescence; whereas the [2,3-d] isomer is known to have fluorescence properties in solution, 5 the [1,2-a] isomer has only aggregation-induced emission enhancement properties. 7 The latter heterocyclic core has not yet been explored in depth by modifying the π-system with different substituents. 6 Some methodologies have been reported that are based on a 2-aminopyrrole and 1,3-dicarbonylic system, as described by Grinev et al, 8 Bao et al, 7 and Huang et al 9 Gevorgyan et al 10 studied the synthesis with 2-alkynylpyrimidine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast, only a few examples of the synthesis of the [1,2- a ] isomer were found in the literature. Consequently, this difference is also observed in the analysis of some properties such as fluorescence; whereas the [2,3- d ] isomer is known to have fluorescence properties in solution, the [1,2- a ] isomer has only aggregation-induced emission enhancement properties . The latter heterocyclic core has not yet been explored in depth by modifying the π-system with different substituents …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation